2021
DOI: 10.1177/23247096211016228
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Spontaneous Pneumomediastinum in a Patient With COVID-19 and Influenza Coinfection

Abstract: Spontaneous pneumomediastinum is reported in patients with coronavirus disease-2019 (COVID-19) and influenza infection independently, usually associated with noninvasive and mechanical ventilation. We report a case of spontaneous pneumomediastinum in a patient with COVID-19 and influenza coinfection. A 58-year-old male admitted with shortness of breath, diagnosed with COVID-19 and influenza infection. A computed tomography angiogram showed pneumomediastinum. He was treated conservatively with 15 L of oxygen, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Pneumothorax due to barotrauma from ventilation, as well as spontaneous pneumothorax due to damage to the alveolar wall, has been reported with a median duration of nine days since the start of symptoms, with a mortality rate of 36% [ 103 , 114 ]. Spontaneous pneumomediastinum in a non-ventilated patient has also been reported [ 115 ]. An autopsy study showed that massive PE can occur in initially asymptomatic COVID-19 patients [ 103 , 116 ].…”
Section: Reviewmentioning
confidence: 99%
“…Pneumothorax due to barotrauma from ventilation, as well as spontaneous pneumothorax due to damage to the alveolar wall, has been reported with a median duration of nine days since the start of symptoms, with a mortality rate of 36% [ 103 , 114 ]. Spontaneous pneumomediastinum in a non-ventilated patient has also been reported [ 115 ]. An autopsy study showed that massive PE can occur in initially asymptomatic COVID-19 patients [ 103 , 116 ].…”
Section: Reviewmentioning
confidence: 99%
“…Pneumothorax due to barotrauma from ventilation as well as spontaneous pneumothorax due to damage to the alveolar wall has been reported with a median duration of nine days since the start of symptoms, with a mortality rate of 36% (103,114). Spontaneous pneumomediastinum in a non-ventilated patient has also been reported (115). In an autopsy study, it was shown that massive PE (pulmonary embolism) can occur in initially asymptomatic COVID-19 patients (103,116).…”
Section: Skinmentioning
confidence: 99%